Influence of iron nanoparticles on rice (Oryza sativa) plant growth and yields - Gobinath, R; Datta, SP; Vijayakumar, S; Singh, RD; Sharma, VK; Surekha, K; Manasa, V (ORYZA-An International Journal of Rice, 2023)
Alleviating iron (Fe) deficiency in soil and enhancing Fe content in edible portions by using conventional supplements pose challenges. In this context, a greenhouse experiment was conducted during the kharif season of 2018 to evaluate the impact of iron dose and source, specifically nano Fe2O3 and FeSO4, on rice root growth and yields. Results showed that foliar application of 0.2% Fe through FeSO4 and 0.2% Fe through nano Fe2O3 significantly increased the mean root length by 9.5% and 10.1%, respectively, alongside increasing the mean root surface area by 8.8% and 7.3%, respectively, over control. However, the soil application of Fe (3 mg Fe/kg and 0.6 mg Fe/kg through nano Fe2O3 was ineffective in enhancing the rice root length and surface area. In contrast to the root parameters, nano Fe2O3 treatment did not have any significant improvement in grain and straw yield. The addition of Fe through FeSO4 .7H2O led to a noteworthy 24% and 33% increase in grain yield at 0.2% Fe (foliar) and 15 mg Fe/kg (soil), respectively. Similarly, the straw yield saw a corresponding increase of 39% and 34%, respectively, over control. Moreover, the application of FeSO4 and nano Fe2O3 resulted in Fe content registering 1.89 and 1.50 times higher than the control (93 mg/kg). Conversely, lower doses of nano Fe2O3 exhibited no influence on ferrous ion content, DTPA-Fe levels, or yield through both foliar and soil applications.